2023
DOI: 10.1002/vms3.1093
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal parasitic infections in wild mammals of a safari park and a zoo in Bangladesh

Abstract: In safari parks and zoos, wild animals are kept mainly for recreational purposes. Animals in these enclosures are also crucial for the education, research, and conservation aspect. To ensure better management and good health of wild animals in captivity, it is essential to monitor the occurrence of gastrointestinal (GI) parasitic (helminths and protozoa) infections. The current investigation was undertaken to investigate the prevalence of GI parasitic infections in wild mammals at Bangabandhu Sheikh Mujib (BSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
2
2
Order By: Relevance
“…The number of species found infected varied according to the zoological institution, being overall and by animal group (according to their diet) higher in ZooAquarium than in Faunia. However, the values found in ZooAquarium are within the range of results published by other authors [ 25 , 31 , 32 , 60 ], and compared to other European zoos, the values are also similar or even lower [ 26 , 34 , 44 , 61 ]. These overall data, however, require a more detailed analysis as there are significant differences depending on the mammalian group considered.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The number of species found infected varied according to the zoological institution, being overall and by animal group (according to their diet) higher in ZooAquarium than in Faunia. However, the values found in ZooAquarium are within the range of results published by other authors [ 25 , 31 , 32 , 60 ], and compared to other European zoos, the values are also similar or even lower [ 26 , 34 , 44 , 61 ]. These overall data, however, require a more detailed analysis as there are significant differences depending on the mammalian group considered.…”
Section: Discussionsupporting
confidence: 87%
“…Among carnivorous animals, we only found positive samples in some species of the order Carnivora and in the giant anteater (order Pilosa) (Tables 3 and 5). In species of the order Carnivora, the vast majority of findings occurred only once or twice over the 10 years of sampling, and except for four positive samples for Capillaria, the parasites now found do not correspond to those generally detected in other studies, which report ascarids, whipworms, and strongyles [13,25,31,34,44,60,62].…”
Section: Mammalian Hostscontrasting
confidence: 79%
“…): 1) Strongyle-type eggs observed in 4 (8.7 %) and 7 (46 %) samples; 2) Moniezia eggs observed in 2 (4.3 %) and 1 (6.7 %) samples; 3) Fasciola eggs observed in 1 banteng sample (2.2 %); 4) Rumen fluke eggs observed in 3 (6.5 %) and 1 (6.7 %) samples; 5) Toxocara eggs observed in 2 cattle samples (13.3 %); and Capillaria, Strongyloides, and Trichuris eggs were identified in a different (6.7 %) sample. The results in the present study showed overall prevalence of 26.2, 17.4, 53.3 % for both animal groups combined, bantengs and domestic cattle respectively, which were much lower than the prevalence in wild animals reported elsewhere [18,19]. Regarding genera diversity, we identified 4 genera in the wild banteng population; whereas, 7 were revealed in the domestic cattle.…”
Section: Resultscontrasting
confidence: 75%
“…The significant finding of a considerable range of GI parasitic infections (62.6% of animals infected) among captive mammals at Khon Kaen Zoo raises concerns. Comparable prevalence values have been reported from zoo populations in other countries, such as Nepal (19.5%) [ 33 ], Malaysia (56.3%) [ 34 ], and Bangladesh (60.5%) [ 35 ]. Higher prevalence has been reported in some cases, such as 68.3% in the Rio de Janeiro Zoo [ 36 ], 72.5% in Spain [ 5 ], and 71.8% and 74.2% in Brazil [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 59%
“…In our study, fecal samples were collected directly from the floor of zoo animal enclosures. This non-invasive approach eliminates the need for chemical or mechanical restraint of the animals, such as Nepal (19.5%) [33], Malaysia (56.3%) [34], and Bangladesh (60.5%) [35]. Higher prevalence has been reported in some cases, such as 68.3% in the Rio de Janeiro Zoo [36], 72.5% in Spain [5], and 71.8% and 74.2% in Brazil [37,38].…”
Section: Discussionmentioning
confidence: 99%